Competency Development of Functional Position Supervisors of Regional Government Implementation through Coaching Model - Sibarani, Togar (Riwayat: Educational Journal of History and Humanities, 2023)
Competency development of the Regional Government Affairs Supervisor (PPUPD) has an important role, because the PPUPD Functional Position is a Civil Servant (PNS) who is given full duties, responsibilities, authorities, rights by the Authorized Official to supervise the implementation of concurrent government affairs. If the PPUPD Functional Position is not competent in carrying out its duties, responsibilities and authorities, individual performance, inspectorate performance will be lower, which has an impact on the vision and mission of government to realize good governance. The problem is, how to develop the competence of the PPUPD Functional Position through a Coaching clinic model that is relevant and effective in producing work competencies that are in accordance with the standards and expectations of the PPUPD Functional Position in supervising the implementation of regional government affairs ? The purpose of this research is to describe the competency level of PPUPD Functional Position based on predetermined competency standards and create a hypothetical model that is relevant and effective for competency development of PPUPD Functional Position. This research uses a descriptive qualitative method with research and development in designing a coaching clinic model that is effectively applied in training institutions. The research findings show that a coaching clinic model is needed to increase the effectiveness of competency development for PPUPD Functional Position with the Goal, Reality, Option, Wrap-Up (GROW) approach, so that there is an increase in the effectiveness of technical competence , especially in risk management material, examination/investigation techniques and forensic examination material which is currently still not optimal.